Ethylene absorption on crystalline and amorphous water ice - Strobush, Kirsten M.; Hooper, Matthew C. (My University, 2007)
We present the results of laboratory investigations of ethylene absorption on amorphous and crystalline water ice films. Water films are grown on a cryostat-cooled, gold-plated copper mirror under high-vacuum at 60 K. They are subsequently annealed at temperatures ranging from 60 to 150 K and then an ethylene layer is deposited at 30 K. The interactions between ethylene and the water ice film change depending upon the thermal history of the water ice film and are characterized using TPD (thermal programmed desorption analysis). Adsorbed films are further characterized by their infrared spectra, which are collected using polarized FT-IRRAS (Fourier transform-infrared reflection absorption spectroscopy) in the spectral range 800-4800 cm-1. Absolute film thicknesses are also measured using a laser interferometric technique.
Color poster with text, graphs and diagrams describing research conducted by Matthew C. Hooper and Kirsten M. Strobush advised by James Boulter.
Keywords: Ethylene--Absorption and adsorption; Liquid crystal films; Posters